Implementasi Keterampilan 4C (Communication, Collaboration, Critical Thinking, And Creativity) Pada Mata Pelajaran Pendidikan Agama Islam di SMK Negeri 1 Jombang - Putri, Sofi Meilina; Ilahiyah, Iva Inayatul (Menara Tebuireng, 2025)
21st century learning emphasizes the importance of 4C skills, namely Communication, Collaboration, Critical Thinking, and Creativity. This study aims to analyze the implementation of 4C skills in Islamic Religious Education (PAI) subjects at SMK Negeri 1 Jombang. The research method used is a qualitative approach with case studies through interviews, observations, and documentation. The results of the study indicate that 4C skills have been applied in PAI learning through various active methods, such as discussions, group work, and creative presentations. Supporting factors for the implementation of 4C skills include teacher competence, school policies, and adequate technology facilities. However, there are still obstacles such as limited learning time and low student motivation. Therefore, stronger school policies and teacher training are needed to improve the effectiveness of the implementation of 4C skills in PAI learning.